Training on Postharvest Guava Fruit Processing in KWT Jambu Biji, VII Koto Sungai Sariak, Pariaman - Yefrida Yefrida; Refilda Refilda; Imelda Imelda; Refinel Refinel; Rahmiana Zein; Safni Safni; Admi Admi; Dheasy Gustira; Jihanul Khaira; Harza Dipajana Umardi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Red guava fruit is one type of fruit that quickly changes colour, texture and spoilage. This is of course a problem for farmers. At harvest time, not all of the fruit is marketable. So sometimes farmers just leave the fruit on the tree, because if harvested it will only increase operational costs. The KWT Jambu Biji Bengke Sakato, VII Koto Sungai Sariak, Pariaman is a group of red guava farmers. They tried to find a solution to this problem by discussing with TIM PPM KIMIA UNAND of the Department of Chemistry, FMIPA, Universitas Andalas. Finally it was agreed that the solution was to make products from red guava. The products made in this program are dodol and red guava ice cream. The KWT members and the Tim PPM KIMIA UNAND together made these two types of products. The results obtained, dodol and ice cream made are quite delicious and have an attractive appearance. This product can be an alternative to red guava processing that has economic value.